SOME SCIENTIFIC AND APPLIED PROBLEMS OF SUPERGENE GEOCHEMISTRY IN THE U.S.S.R - Lukashev V.K. (My University, 1986)
Demands of modern human society require a wide application of the principles of hypergene geochemistry in order to explore for deeply buried minerals, protect the environment, assist in some medical and biological problems, etc.; such is impossible without a sound theoretical basis for this science. It is necessary that the processes associated with deep weathering be investigated, as well as the mechanisms of element transport (electrochemical transfer, vapor transport, migration of elements in pore water, etc.) and the formation of geochemical halos in various secondary environments. More effective techniques (based on chemical extractions, artificial sorbents, biological methods, etc.) must be developed in order to make further advances in all aspects of applied supergene geochemistry. Toward this end, the successful application of artificial sorbents to exploration and environmental problems is illustrated, and “geochemistry of technogenesis”, one of the main branches of hypergenesis, is discussed and shown to be presently at the stage of “geochemical inventory”. Technogenic geochemistry consists of detailed data collection for all elements and, primarily, geochemical mapping of affected environments. One of the objectives of technogenic geochemistry is the development of the theory and implementation of practical measures necessary to utilize the most efficient geochemical systems in the various natural situations affected by man. Lack, or excess, of certain chemical elements in the environment are important geochemical factors to be considered in the study of endemic disease (i.e. “medical geochemistry”). Studies are illustrated which show a general tendency for areas with higher percentages of cancer to have higher average contents of Mn, Pb and Co, but lower amounts of Cu, compared with regions with moderate oncological disease rates. The importance of studying the modes of occurrence of chemical elements in the secondary environments is stressed. By the end of this century the role of environmental geochemistry is expected to be substantially more important and will require scientists specifically trained in this subject.